(3eLehYI aj GdcjejGAs - (3LGeGSas
(3ChdgG (B:s
(3ef GdVYja GdeScjf Hf GdeSGcjf LGeGSa GdPi GNJUegY Gddg HGYdWjI GdcQjeI haJb GdYdhe GdZGeVI EYde CjgG Gdedc GdeDjO Efc dSJ HHGdZ TjFkG eG jWdH HGdYde hGdYed GdPi LYdg Gddg SJQkG ddMceGA s
(3BNQgG (B:s
(3MJi jUHZ GdPgH GdNGdU Ef TGA Gddg JYGdi bO HfjfG GdYed JGekG hbdJ ajgG eGde jbd GMO JeJ QSGdI LGeGSa ai JYdje GdMceI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHYs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1407s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs